The Effect of Tax Disputes on Firm Value (Analysis Based on Signal Theory and RBV Theory) - Naniek Noviari; I Gusti Bagus Wiksuana; IB Panji Sedana; I Putu Sudana (Jurnal Bisnis dan Kewirausahaan, 2022)
Tax dispute cases in Indonesia is increasing during 2014-2020. The potential risk of Taxpayer losing in a tax dispute is relatively high (48%). On the other hand, the voluntary disclosure of tax disputes in the published Company Report is of great concern to the stakeholders. This article aims to examine the theory and previous studies that explain the correlation among voluntary disclosure of tax disputes and firm value. The analysis is complemented by a systematic compilation of literature on research issues and results so that future research directions are obtained. In this research Signal Theory was developed by combining it with RBV theory. The variables of political connection and the profile of a tax consultant licensed by a lawyer were added as moderating variables. This will make Signal Theory more comprehensive in verifying the correlation among voluntary disclosure of tax disputes and company value.